Reconstruction of 3D Foot Model from Video Captured Using Smartphone Camera (Journal of Fiber Bioengineering and Informatics, 2015)
In this paper, a method is proposed to reconstruct 3D foot model using video captured by smart phone.Scale-Invariant Feature Transformation followed by feature matching were adopted to generate consistenttracks. These tracks were further processed to generate 3D points in terms of Structure-from-motion(SFM). The accuracy of the proposed method was evaluated by comparing the difference between thereconstructed foot and the scanned foot of an artificial socked foot. The mean error between them was0.15 mm (SD=1.42 mm). Almost 80% data had an error less than 1.5 mm. The experimental resultsindicated that a mapped 3D foot model could be reconstructed by this simple and efficient method, andthe accuracy of this method is enough for foot measurement and footwear design.